Vitamin D Trajectories and Cardiometabolic Risk Factors During Childhood: A Large Population-Based Prospective Cohort Study - Xiao, Pei; Cheng, Hong; Li, Haibo; Zhao, Xiaoyuan; Hou, Dongqing; Xie, Xianghui; Mi, Jie (Frontiers in Cardiovascular Medicine, 2022)
Background and Objectives: Vitamin D has been indicated to play an important role in the optimal function of cardiovascular system. However, with limited evidence, it remains unclear whether vitamin D status transition during childhood would affect cardiometabolic risk factors. Thus, we aimed to identify the associations of the longitudinal trajectory of vitamin D status with cardiometabolic risk factors in children. Methods: A total of 10482 participants with complete follow-up records from a large population-based prospective cohort study were included in this analysis. The 25-hydroxyvitamin D (25[OH]D) concentrations, blood pressure, blood lipids, and fasting blood glucose were determined. Based on the vitamin D status at baseline and follow-up, we identified four possible trajectories: 1) persistent non-deficiency (reference); 2) baseline non-deficiency to follow-up deficiency; 3) baseline deficiency to follow-up non-deficiency; 4) persistent deficiency. The relationships between cardiometabolic risk factors and vitamin D trajectories were evaluated using adjusted risk ratios. (RRs) Results: Overall, 35.1% and 24.2% of participants had vitamin D deficiency at the baseline and follow-up, respectively, and 15.1% were under the condition of persistent vitamin D deficiency. Compared to children with persistent non-deficiency, those who shifted from non-deficiency at baseline to deficiency at follow-up had a 2.09-fold (95%CI: 1.36, 3.23) increased risk of high triglyceride (TG). Besides, children with altered vitamin D status from deficiency to non-deficiency during follow-up were still at a significantly higher risk of high total cholesterol (TC) than the reference group (RR [95%CI]: 1.61 [1.18, 2.19]). Finally, children with persistent vitamin D deficiency were at the highest risks of high TC (RR [95%CI]: 1.61 [1.18, 2.19], Ptrend<0.001), high low-density lipoprotein cholesterol (LDL-C) (RR [95%CI]: 1.53 [1.04, 2.27], Ptrend=0.046), and high TG (RR [95%CI]: 1.96 [1.34, 2.87], Ptrend=0.003). Conclusion: Our results suggest that persistent vitamin D deficiency might increase the risk of dyslipidemia in children, and vitamin D deficiency could have has short- and long-term effects on TG and TC, respectively.